Ultrafast femtosecond pressure modulation of structure and exciton kinetics in 2D halide perovskites for enhanced light response and stability - Chunpeng Song (Nature Portfolio, 2021)
Exciton in two-dimensional perovskite is strongly influenced by dielectric confinement of the organic components. Here, the authors employ femtosecond laser to induce ultrashock pressure to investigate how the structural changes and the reduction of dielectric confinement affects exciton behaviour and dynamic.